Individual preferences for scented water bowls in dogs - Sonowal, Rituparna; Hall, Nathaniel J.; Stellato, Anastasia C. (Frontiers in Veterinary Science, 2025)
IntroductionWhile food preferences have been extensively studied, much less is known about water preferences in dogs, especially regarding preferences for non-consumptive scented items attached to water bowls. As a form of sensory enrichment, scents can increase engagement and were used here to assess whether dogs show individual scent preferences when drinking water. This research explores whether individual preferences for non-consumptive scented sleeves on the water bowl influence dogs’ water consumption, considering that adequate hydration is vital to their health and physiological functions. Establishing individual preference for such items may promote hydration in dogs, which could support maintaining hydration levels for dogs, especially those with existing health conditions.MethodologyExperiment 1 evaluated the water consumption levels of dogs (N = 20) in household settings over 4 days using four bowls with sleeves (three scented and one non-scented). Each bowl was placed on a custom-built scale to record daily water consumption (mL/kg) to establish the individual bowl preference. Experiment 2 recruited dogs (N = 10) from Experiment 1 to record water consumption over 14 days using two bowls embedded with sleeves preferred scented emulsified sleeves (based on Experiment 1; chicken or beef, and non-scented). Owners completed a brief survey to report their dog’s diet type, daily physical activity levels (<30 min, >30 min – 1 h, >1 h), method of feeding (free-fed or scheduled), and dog age.ResultsIn Experiment 1, there was no single scent that was preferred across dogs (p = 0.15). In Experiment 2, dogs had greater water consumption with their preferred emulsified scented sleeves compared to the non-scented (p = 0.02). Increased water consumption was associated with dry diet (p = 0.02) and most water consumption occurred during the evening (p < 0.001; vs. afternoon). Age and daily physical activity levels did not influence water consumption in dogs.DiscussionFindings suggest that using emulsified scented sleeves is associated with water consumption preference in pet dogs, and their preference for a scented sleeve over a non-scented one was sustained across experiments and through the 14-day data collection period. Thus, dogs prefer to consume water from water bowls with scented sleeves, which may be helpful with hydration and should be investigated in future work.